Development and validation of Chinese college students’ future employability scale - Chen, Wanyu; Shao, Kaixu; Xiao, Qiuye; Mai, Yilan (Frontiers in Psychology, 2023)
The spread of COVID-19 and the surge in the number of college graduates have made the dilemma of "fierce competition and difficult employment" always exist. The employment of college students has become a topic of wide concern in the society. This study aims to develop the Future Employability Scale for the Chinese college students and evaluate the reliability and validity. Based on the analysis of the literature, the study made up the initial measurement scale of the college students' future employability, and formed the initial measurement and question volume based on the expert's judgment. Firstly, the students' group was measured, and the data collected by 389 university students were collected and analyzed. Secondly, the data collection and verification factor analysis of 387 university students were collected and verified, and the internal consistency reliability, split-half reliability and validity of the scale were evaluated. In addition 68 college students were selected to evaluate their test-retest reliability after an interval of one month. The Future Employability Scale of college students was composed of 28 subjects which include four dimensions: knowledge skill, personality quality, interpersonal network and career development. The reliability test found that the Future Employability Scale total scale and the internal consistency reliability, split-half reliability and retest reliability of each dimension were good, and the validity test suggested that the scale had good content validity, structural validity and calibration correlation validity. With a clear structure and good reliability and validity, the future employability scale is a good tool to measure the future employability of college students.